SURVEI KEBERAGAMAAN PELAJAR SLTA (Paham Ke-Islaman Pelajar SMA dan MA dalam Kehidupan Sosial) - Suprapto Suprapto (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2012)
Within this last decade many people/ institution/media launch the height of religious intolerance action in Indonesia. Religious intolerant attitude has also been growing among students, Wahid Institute released the rulets of their research finding that religious intolerance attitude of students increasingly flourished, reflected in 49.5% 0f respondents rejected the worship house existence of other religion near their residences. Religious intolerant attitude among students is’thought to have led to the movement of radicalism. It can be said that religious “piety” level of high school muslim students affected the intolerance attitude, if the religious piety of high school Muslim student became stronger, resulting in stronger of intolerant behaviour among muslim hight school students. This study used a quantitative approach.